1937
DOI: 10.1180/minmag.1937.024.157.01
|View full text |Cite
|
Sign up to set email alerts
|

The paragenesis of Cookeite and hydromuscovite associated with gold at Ogofau, Carmarthenshire

Abstract: This paper describes occurrences of cookeite (not previously recorded as a British species) and hydromuacovite, associated with auriferous pyrite and arsenopyrite, blende, galena, carbonates, and free gold at Ogofau, on the left bank of the river Cothi, half a mile ESE. of Pumpsaint, Carmarthenshire.The hillside around Ogofau is scarred with opencast workings and trenches reputed to be an 'ancient gold mine' dating back to Roman times. Though the mine is described as 'disused' on the Ordnance Survey map (six-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1954
1954
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Cookeite is a di, trioctahedral chlorite (Table 1), meaning that the 2:1 layer is dioctahedral and the interlayer is trioctahedral [Bailey, 1980]. Brammall et al [1937] give (Li, A14)(Si3A1)O•0(OH)8 as the ideal formula for cookeite which is a common alteration product of Li-rich materials in pegmatites and hydrothermal veins. Spectrally, cookeite is very different from the trioctahedral chlorites.…”
Section: Car-1 (Cookeite)mentioning
confidence: 99%
“…Cookeite is a di, trioctahedral chlorite (Table 1), meaning that the 2:1 layer is dioctahedral and the interlayer is trioctahedral [Bailey, 1980]. Brammall et al [1937] give (Li, A14)(Si3A1)O•0(OH)8 as the ideal formula for cookeite which is a common alteration product of Li-rich materials in pegmatites and hydrothermal veins. Spectrally, cookeite is very different from the trioctahedral chlorites.…”
Section: Car-1 (Cookeite)mentioning
confidence: 99%
“…These features were previously described in detail for cookeite related to the pegmatite occurrence (Quensel, 1937;Sahama et al, 1968Sahama et al, , Č erný et al, 1971. Brammall et al (1937) reported the same physical characteristics for cookeite present in an ancient gold mine, associated with cleaved blue-black shales and mudstones. Under the polarized light microscope in polished thin section, cookeite occurs as a fine-grained flaky aggregates matrix, radiating fibrous aggregates with pseudo-hexagonal edges like a hemispherical aggregate (Fig.…”
Section: Petrography and Sem Observationmentioning
confidence: 68%
“…If, however, about 50 per cent of the interstratified material is considered to be similar in composition to the beidellite previously discussed, the hydrous mica constituent will have the following calculated formula: Ca0.14Na0.06Kl.a3 (Si6, ~6All.74)(A13.gsFe3+0.02)0 2(0H)a very similar to the hydromnscovite described by Brammall, Leech and Bannister (1937). A K-saturated sample of this beidellite-hydrous mica mixedlayer clay mineral showed basal diffraction peaks at 11.33 A and 24.52 A (Fig.…”
Section: Mineralogy Of the Depositmentioning
confidence: 69%